The relationship of promoting children's literature in the library and the english scores in the NEAT in selected private schools in Marikina City - Domingo, Jo-Anne A. (2002)
The principal aim of the school librarian is to bring children and books together. Thus, they are adapting the motto, "The right book for the right child at the right time". Knowing the meaning of this motto, the librarian must realize the role reading and libraries play in the child's learning. How the child comprehends all that he has learned in his readings in his early age might be determined as the child grows, through various assessment tools like achievement tests, such as the National Elementary Achievement Test (NEAT), administered to Grade VI students. This will be used to determine the performance of pupils to various subject areas, specifically in English, and to know how effective early readings, in upholding the cognitive development of the child.